COMMENTS ON THE ARTICLE AUTHORED BY M.V. MINTS AND K.A. DOKUKINA – THE BELOMORIAN ECLOGITE PROVINCE (EASTERN FENNOSCANDIAN SHIELD, RUSSIA): MESO-NEOARCHEAN OR LATE PALEOPROTEROZOIC? - S. G. Skublov; A. V. Berezin; L. I. Salimgaraeva; С. Г. Скублов; А. В. Березин; Л. И. Салимгараева (Applied Earth Science, 2021)
The comments are given on the article authored by M.V. Mints and K.A. Dokukina – The Belomorian Eclogite Province (Eastern Fennoscandian Shield, Russia): Meso-Neoarchean or Late Paleoproterozoic? (Geodynamics & Tectonophysics 2020, 11 (1), 151–200). The Belomorian (White Sea) province of the Fennoscandia Shield is a key site for studying the tectonics of the early periods because numerous Precambrian eclogites have been found there. It was not anticipated, but the problem of age determinations of the eclogite metamorphism of gabbroids in the White Sea mobile belt has turned out to be extremely relevant not only for this region, but also for the Precambrian geology in general. The reason is that a number of authors determine the age of eclogites as Archean (2.7–2.8 Ga), which makes the White Sea mobile belt the only example of the Archean eclogite metamorphism in the world and, therefore, the only dated evidence in support of the plate tectonic model of the evolution of the Earth’s crust at the earliest stage of its formation. The article consistently provides a critical analysis of the arguments put forward by the supporters of the Archean age of the eclogites of the White Sea mobile belt. Special emphasis is made on the isotope geochronological and geochemical features of the composition of zircons from eclogite samples, as well as on the phase and chemical compositions and distribution patterns of mineral inclusions. Considering the age of eclogite metamorphism that led to the formation of eclogites in the White Sea mobile belt, we propose our interpretation based on a set of independent isotope geochemical dating methods, including the local U- Pb method for heterogeneous zircons with magmatic cores and eclogite rims, the Lu-Hf and Sm-Nd methods for the minerals of eclogite paragenesis (garnet and omphacite). And this age interpretation is fundamentally different from the one described in the commented article: all the three methods independently determine the eclogite metamorphism as Paleoproterozoic and ...